2017
DOI: 10.18869/nirp.bcn.8.5.419
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Face Recognition in Children With Attention Deficit/Hyperactivity Disorder: Evidence From Event Related Gamma Oscillation

Abstract: Introduction:Children with attention-deficit/hyperactivity disorder (ADHD) have some impairment in emotional relationship which can be due to problems in emotional processing. The present study investigated neural correlates of early stages of emotional face processing in this group compared with typically developing children using the Gamma Band Activity (GBA).Methods:A total of 19 children diagnosed with ADHD (Combined type) based on DSM-IV classification were compared with 19 typically developing children m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
1
3
0
1
Order By: Relevance
“…Thus, the average power of the induced neural oscillatory activities in the gamma band (30-40 Hz), based on the 250-to 800-ms post-stimulus window, were extracted for the following statistical analysis. The center of induced gamma activity for construction-site pictures was over the parieto-occipital electrodes during the 0.25-0.8 s period (Figure 5b), in line with previous findings indicating a relationship between brain activity and visual information processing (Razavi et al, 2017).…”
Section: Eeg Power Resultssupporting
confidence: 91%
“…Thus, the average power of the induced neural oscillatory activities in the gamma band (30-40 Hz), based on the 250-to 800-ms post-stimulus window, were extracted for the following statistical analysis. The center of induced gamma activity for construction-site pictures was over the parieto-occipital electrodes during the 0.25-0.8 s period (Figure 5b), in line with previous findings indicating a relationship between brain activity and visual information processing (Razavi et al, 2017).…”
Section: Eeg Power Resultssupporting
confidence: 91%
“…Most studies (21 in the qualitative synthesis, 11 in the meta-analysis) investigated differences between ADHD and control groups in event-related alpha power, with fewer studies reporting effects for theta power (15 in the qualitative synthesis, 7 in the meta-analysis) and beta power (9 in the qualitative synthesis, 5 in the meta-analysis). Only 5 studies, none of which provided sufficient data for inclusion in the meta-analysis, examined gamma power (Baijot et al, 2017;Karch et al, 2012;Leroy et al, 2018;Sarraf Razavi et al, 2017;Yordanova et al, 2001). None of the eligible studies tested delta power.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Muszkat et al (2015) suggested that FER deficits might be attributed to poor allocation of attention to specific cues (Muszkat et al, 2015). Consistent with this, some authors have proposed that deficits in sustained attention and visual processing play a role in FER, as supported by the observation of increased gamma oscillations in occipital regions during the early stages of facial emotion processing (Sarraf Razavi et al, 2017). Additionally, more robust functional connectivity has been observed in the frontal lobes of children with ADHD, which may indicate the abnormal transfer of information from the occipital lobe to the frontal lobe, that is, from the visual to the emotional processing center (Ansari Nasab et al, 2022).…”
Section: Inattentionmentioning
confidence: 80%